Conectando territorios y sociedades. La movilidad de los misioneros jesuitas en el mundo ibérico (siglos XVI-XVIII) - Maldavsky, Aliocha (2014)
The object of this article is to study the mobilization of members of the Society of Jesus, as an example of the connection between different European and American territories in the early modern Spanish monarchy. It also reflects on the relation which might exist, in a Hispano-American world characterized by a situation of colonial domination and the birth of new societies and territories, between the mobility of members of religious orders and their ties to the local population.